Penggunaan Katakana dalam Facebook - Rossy Kumala Sari; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThere were many Japanese uses katakana to write wago in their status and comment in the facebook (a social network site). This situation makes writer interested to research about the using of katakana’s function on wago. To research this problem, the writer used descriptive method.Based on study results on Japanese speakers in some status and comments in the facebook that written in 2013, the authors concludes that there are some functions to use katakana on wago. Most common function is to give emphasis and attract the attention of the reader. The emphasis is expressed by different words, for example: adjectives, nouns, speech, and others. The other functions that found in this study are to write the name of the animal and to write nouns proper name.Keywords: function, uses, katakana, facebook